Synthesis of SrO.SiO2 Catalyst and Its Application in the Transesterification Reactions of Soybean Oil - Nuni Widiarti; Lisa Amalia Suryana; Nanik Wijayati; Endah Fitriani Rahayu; Harjito Harjito; Samuel Budi Wardhana; Didik Prasetyoko; Suprapto Suprapto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
The synthesis and characterization of SrO.SiO2 were carried out. The rice hull ash was utilized as a source for SiO2. The SrO.SiO2 was prepared by sol-gel technique, and the ratios of SrO:SiO2 were varied as 0:1, 1:0, 3:2, 2:4, and 2:7. The sol-gel was calcined at 800 oC for 4 hours. The result was characterized using XRD and FTIR. The diffraction pattern shows that the diffraction angle was shifted, and the intensity of the main peaks was increased. This research indicated that the crystallinity of SrO was improved at the higher SiO content. Further, a new peak was observed in the IR spectra at a wavenumber of 900 cm-1 indicating the appearance of new functional groups of the SrO.SiO2. The catalytic activity of SrO.SiO2 on transesterification reaction was optimized. The optimum condition was obtained at SrO.SiO2 of 2:7, reaction time of 30 minutes, reaction temperature of 65 oC, the amount of catalyst of 1 % w/v of reactants, and the biodiesel yield of 96.66 %.